Finite element modelling of limiting dome high sheet metal formability test - Mohammad Amir, Hashim (2009)
Sheet metal forming is a complex process because it involves many stress state and plastic deformation. So analysis in Limiting dome high test is performing to analyze the criteria of sheet metal. The Limiting Dome High Test is used to evaluate press formability of sheet metal. The Limiting Dome Height (LDH) test is a modified hemispherical dome test. Instead of a fully clamped blank, strips of varying widths are clamped on end by a lock bead and then deformed with hemispherical punch. In order to understand the origin of the widely varied results, a sensitivity study was performed using finite element modeling (FEM). The finite element method (FEM) is a computational technique used to obtain approximate solution of boundary value problems in engineering. The effect of dimension -in doing the analysis in Finete Element Modelling is important to make sure the analysis is completely rigth will analyze. The effect of draw bead clamps between blank holder and upper die are influneces the formablity of sheet metal deformed. Elastically and plastically carateria of each material also are influences the rate of forming and shape of the deformation. The analysis in ALGOR V22 software, one of Finite Element Modelling software are use to analyze the sheet metal formabilty. The design, meshing, type of element parameters, analysis type, material properties, Finite Element Analysis Object contain by boundary condition and prescribed dispalcement are used. The result of anlysis is about of the caracteristic of node at sheet metal movement due to displacement in y direction are consider, and the plastic equivalent strain also determined from the anlysis. Thus the displacement and maximum equivalent plastic strain of different material can evalute and compared.